FRI0026 Correlation between Serum Rituximab Level and Clinical Response in Rheumatoid Arthritis Patients Treated with B Cell Depletion Therapy. (10th June 2014) - Diana, M.; Iliuta, M.; Gainaru, C.; Luca, G.; Apetrei, N.; Gudu, T.; Peltea, A.; Constantinescu, C.; Groseanu, L.; Bojinca, V.; Saulescu, I.; Borangiu, A.; et al.
Abstract : Background: Rituximab (RTX) sustained efficacy in rheumatoid arthritis (RA) patients can be achieved by repeated courses of RTX (1). The correlation between serum drug level before a new retreatment and clinical response remains to be established. Objectives: To investigate the relationship between serum RTX level just before a new retreatment course and clinical response after 6 months. Methods: Twenty five consecutive RA patients treated with RTX for more than 12 months were included in this prospective study initiated in May 2013 and followed up until December 2013. Serum samples were collected for assay of drug level and anti-drug antibodies (ADAb) using sandwich ELISA (Promonitor-RTX Ref.PG-PRTX-12700). Patients were divided according to RTX serum level into detectable versus non-detectable drug level based on assay cut-off. Their disease activity was assessed by Disease Activity Score (DAS28) and Simplified Disease Activity Index (SDAI) scores at baseline and after 6 months of follow-up. At follow-up they were classified using DAS28 score in patients with high, moderate, low disease activity and remission. The unpaired t-test or, where appropriate, Wilcoxon Mann-Whitney test, was used for comparisons. Results: At baseline, 8 (36%) patients had non-detectable RTX level with mean DAS28 and SDAI score of 3.45 and 21.79 respectively. Six (66.6%) of them had moderate or high disease activity compared to 75% of patients in the RTX detectable group. At the time of follow-up (6 months after dosing RTX), 5 patients with no-detectable RTX level achieved low disease activity or remission, compared to 11 patients with detectable serum RTX. Patients with detectable RTX level showed larger reduction of DAS28 and SDAI score at follow-up (P=0.0104, respectively P=0.0332), versus patients with undetectable RTX level. Lower disease activity class was achieved in patients with detectable drug serum level (P=0.0036). All patients tested negative for ADAb. Conclusions: This pilot prospective study suggests that detectable RTX serum level just before re-treatment is correlated to further clinical response in RA patients. The results of our study are promising for the optimization of treatment responses and easy applicable in clinical practice. References: Mok CC. Rituximab for the treatment of rheumatoid arthritis: an update. Drug Des. Devel. Ther. 2014;8(87-100). Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.4831